Effect of thermophysical property of energy pile on heat transfer based on the dimensionless analytical solution. Issue 7 (October 2021) - Yan, Zhenguo; Zeng, Shu; Yang, J
Abstract: Energy pile, as the heat exchanger extracts heat from the ground, is gradually accepted by engineers. When using it, enhancing the heat transfer power is the critical factor, and there are many ways to achieve this goal. This paper analyses the effects of the energy pile's thermophysical property changing on the heat transfer via using the dimensionless mathematical model. Firstly, it transformed the mathematical model from the literature [1] to a dimensionless form. After obtained the analytical solution, the calculation results verified that the correctness of a dimensionless analytical answer. On this basis, discussed the effect of the difference of thermophysical properties between the pile and surrounding soil on heat transfer in typical heat transfer time. The results show that thermal conductivity difference affects heat transfer during the whole heat transfer period. In contrast, the diversity of volumetric heat capacity affects the heat transfer only at the initial stage of heat transfer and the pile's thermal conductivity is small. Therefore, engineers should fully consider the thermophysical properties difference between the pile and surrounding soil. To improve the heat transfer of the energy pile, enhancing thermal conductivity is the most effective way.